Inflammation and infection in human cocaine addiction. (February 2017) - Ersche, Karen D; Döffinger, Rainer
Highlights: High levels of infection in cocaine addiction cannot be explained by risk-taking behaviour alone. Chronic cocaine use seems to be associated with a decline in immune responsiveness. The implication of cocaine's immunomodulatory effects may go beyond infection susceptibility. Abstract : Over the past 30 years, the effects of cocaine on the immune system have been subject to research mainly in animals, while relatively little work has been done in humans. This review focuses exclusively on the human work and the related findings in a way that is accessible to neuroscientists. The emerging picture suggests that cocaine may exert some direct effects on lymphocyte responses, as well as, and possibly more importantly, indirect effects via interactions with the sympathetic and neuroendocrine systems. Given the pressing need for more effective treatments for cocaine addiction and the high prevalence of medical complications associated with this disorder, this review leaves no doubt that drug addiction merits a place in the growing field of neuropsychoimmunology.